MiR-135b protects cardiomyocytes from infarction through restraining the NLRP3/caspase-1/IL-1β pathway. (15th May 2020) - Li, Anqi; Yu, Yahan; Ding, Xueying; Qin, Ying; Jiang, Yanan; Wang, Xinyao; Liu, Guanqun; Chen, Xi; Yue, Er; Sun, Xi; Zahra, Syeda M.; Yan, Yan; et al.
Abstract: Background: Myocardial infarction (MI) is the most common cause of cardiovascular morbidity and mortality worldwide. Despite the identification of many pathogenic genes associated with MI, the underlying molecular mechanisms remain poorly understood. MicroRNAs (miRNAs, miRs), which regulate target genes at the post-transcriptional level, play a significant role in the regulation of cardiovascular diseases such as MI. Pyroptosis is a caspase-1-dependent pro-inflammatory programmed cell death (PCD) mechanism. The role of pyroptosis in several diseases associated with various miRNAs has been studied extensively. Meanwhile, the role of NOD-like receptor-containing pyrin 3 (NLRP3)/caspase-1/interleukin-1β (IL-1β) pathway in cardiac diseases has also been more recognized. Methods: We established a mice MI model which ligated with the left anterior descending coronary artery and a cardiomyocytes injury model treated by hydrogen peroxide (H2 O2 ) to detect the expressions of miR-135b and NLRP3/caspase-1/IL-1β pathway. Then miR-135b mimic, agomir-135b, and α-MHC-miR-135b transgenic mice were used to evaluate the effects of miR-135b overexpression. Result: We demonstrated that miR-135b was downregulated after cardiomyocytes injury both in vivo and in vitro. Pyroptosis pathway was also activated. MiR-135b overexpression remarkably restored impaired cardiac function and attenuated the upregulation of NLRP3/caspase-1/IL-1β pathway. Conclusions: The present findings shed light on the protective role of miR-135b in MI mediated by the inhibition of the NLRP3/caspase-1/IL-1β pathway. Highlights: NLRP3/caspase-1/IL-1β pathway is activated in MI model. MiR-135b could inhibit pyroptosis by targeting caspase-1 during MI. MiR-135b plays a protective role in MI. MiR-135b alleviates MI injury by inhibiting the NLRP3/caspase-1/IL-1β pathway.